Labour market marginalisation among refugees from different countries of birth: a prospective cohort study on refugees to Sweden. Issue 5 (12th February 2019) - Helgesson, Magnus; Wang, Mo; Niederkrotenthaler, Thomas; Saboonchi, Fredrik; Mittendorfer-Rutz, Ellenor
Abstract : Background: The aim was to elucidate if the risk of labour market marginalisation (LMM), measured as long-term unemployment, long-term sickness absence, disability pension and a combined measure of these three measures, differed between refugees and non-refugee migrants with different regions of birth compared with native Swedes. Methods: All non-pensioned individuals aged 19–60 years who were resident in Sweden on 31 December 2009 were included (n=4 441 813, whereof 216 930 refugees). HRs with 95% CIs were computed by Cox regression models with competing risks and time-dependent covariates with a follow-up period of 2010–2013. Results: Refugees had in general a doubled risk (HR: 2.0, 95% CI 1.9 to 2.0) and non-refugee migrants had 70% increased risk (HR: 1.7, 95% CI 1.7 to 1.7) of the combined measure of LMM compared with native Swedes. Refugees from Somalia (HR: 2.7, 95% CI 2.6 to 2.8) and Syria (HR: 2.5, 95% CI 2.5 to 2.6) had especially high risk estimates of LMM, mostly due to high risk estimates of long-term unemployment (HR: 3.4, 95% CI 3.3 to 3.5 and HR: 3.2, 95% CI 3.1 to 3.2). African (HR: 0.7, 95% CI 0.6 to 0.7) and Asian (HR: 1.0, 95% CI 1.0 to 1.1) refugees had relatively low risk estimates of long-term sickness absence compared with other refugee groups. Refugees from Europe had the highest risk estimates of disability pension (HR: 1.9, 95% CI 1.8 to 2.0) compared with native Swedes. Conclusion: Refugees had in general a higher risk of all measures of LMM compared with native Swedes. There were, however, large differences in risk estimates of LMM between subgroups of refugees and with regard to type of LMM. Actions addressing differences between subgroups of refugees is therefore crucial in order to ensure that refugees can obtain as well as retain a position on the labour market.